Efektivitas Multi-bi Aid pada Greater Mekong Sub-region (GMS) Triangle Project - Devita Prinanda (Sospol : Jurnal Sosial Politik, 2018)
The existences of geographical factors, push factors and pull factors generated the intensity of migration in Greater Mekong Sub-Region (GMS). The region which consists of Cambodia, Lao PDR, Myanmar, Thailand, Vietnam, and part of China’s territory had various problems in the migration process.  A predominant problem of migration is rendered by the absence of law framework. Therefore, there were a practically illegal migrant and human trafficking. This research will explain the assistance to recover migration’s problems in GMS given by Australian Government (cooperated with ILO). The type of assistance is categorized as multi-bi aid which is the assistance given by the bilateral donor to a multilateral institution. The assistance was released in the form of a project named GMS Triangle Project with the aim of creating migrant protection in GMS. To analyze the implementation of that project, the author uses the concept of multi-bi aid and review effectiveness through the concept of aid effectiveness proposed by Paris Agreement including ownership, alignment, harmonisation, managing for a result, and Mutual Accountability. The result of this study describes how multi-bi aid methods are embodied in a form of project and effectiveness are different for each receiving state in GMS.